Synthesis, Characterization and Microbial Study Via Some New Salbutamol’s Derivatives - Fenjan, Abdel-Amir M; Dhahir, Saadiyah A; Al-Sahib, Sanaa A; Thanoon, Shatha (Al-Nahrain Journal of Science, 2018)
During this work, some new medical salbutamol,s derivatives were prepared, characterized and their biological activity was determined. A simple and efficient procedure for obtaining 4-(1-oxoacetyl-2-tert-butylaminoethyl)-6-methanolyl phenol 2 (acetylated salbutamol 2) from a reaction between acetic anhydride and 4-(1-hydroxy-2-tert-butylaminoethyl)-6-methanolyl phenol 1 (salbutamol 1) in an acidic medium was reported. A coupling reaction between the diazonium salts of aniline derivatives with an acetylated salbutamol 2 gave the new corresponding azo derivatives in the selective yields. These compounds were characterized by various physical techniques like: FTIR spectra, UV-Visible spectra, determination of the total number of hydroxyl groups of an acetylated salbutamol 2, melting point and the evaluation of microbial activity in vitro against Gram +Ve, Gram Ve bacteria and fungi. A potent antibacterial activity was noticed only for the following compounds: 2-(2’,4’-Dichloroazophenyl)-4-(1-oxoacetyl-2"-tert-butylaminoethyl)-6-methanolyl phenol 3. 2-(2’,3-Dimethylazophenyl)-4-(1-oxoacetyl-2"-tert-butylaminoethyl)-6-methanolyl phenol 5. 2-(5-Mercapto-1’,3,4’-thiadiazol-2’-azoyl)-4-(1-oxoacetyl-2"-tert-butylaminoethyl)-6-methanolyl phenol 6.